2016
DOI: 10.1152/ajpendo.00042.2016
|View full text |Cite
|
Sign up to set email alerts
|

Reduced intestinal lipid absorption and body weight-independent improvements in insulin sensitivity in high-fat diet-fed Park2 knockout mice

Abstract: Shulman GI, Jurczak MJ. Reduced intestinal lipid absorption and body weight-independent improvements in insulin sensitivity in high-fat diet-fed Park2 knockout mice. Am J Physiol Endocrinol Metab 311: E105-E116, 2016. First published May 10, 2016; doi:10.1152/ajpendo.00042.2016.-Mitochondrial dysfunction is associated with many human diseases and results from mismatch of damage and repair over the life of the organelle. PARK2 is a ubiquitin E3 ligase that regulates mitophagy, a repair mechanism that selectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 56 publications
4
23
1
Order By: Relevance
“…Whole body siRNA of NTSC2 in mice showed increased lipolysis [ 13 ] and VTI1A was shown to interact with GLUT4 in adipocytes in mice[ 14 ]. More directly, PARK2 KO mice show decreased fat absorption and are leaner on high-fat diets[ 15 ]. VASP KO mice have reduced body weight and increased brown adipocytes[ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Whole body siRNA of NTSC2 in mice showed increased lipolysis [ 13 ] and VTI1A was shown to interact with GLUT4 in adipocytes in mice[ 14 ]. More directly, PARK2 KO mice show decreased fat absorption and are leaner on high-fat diets[ 15 ]. VASP KO mice have reduced body weight and increased brown adipocytes[ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Further mechanical studies implied that Parkin conferred these effects via ubiquitin-mediated stabilization of the lipid transporter CD36 in the liver [141,142]. Interestingly, in an acute HFD feeding model, impaired intestinal lipid absorption was found in Parkin knockout mice as evidenced by increased fecal lipids and reduced plasma triglycerides after intragastric fat challenge, while intravenous lipid infusion can cause liver steatosis in the knockout mice [143]. These results highlight the essential role of Parkin in regulating lipid absorption besides mediating mitophagy, which may contribute to the contrary effects of Parkin deficiency in alcohol and HFD-induced liver injury.…”
Section: Mitophagy In Nafldmentioning
confidence: 99%
“…Not surprisingly, HFD‐fed Park2 KO mice displayed improved glucose and insulin tolerance when compared with obese HFD‐fed wild‐type (WT) mice, but it was unclear whether changes in liver fat and glucose homeostasis after HFD feeding were due to loss of Park2 or secondary to the protection from obesity (Kim et al, ). To address this question, we fed Park2 KO mice a short‐term, one‐week HFD in order to induce hepatic insulin resistance without major changes in body weight (Costa et al, ). Under these conditions, body fat was modestly reduced by 1.2 g or 5% in Park2 KO mice, but there was no difference in body weight.…”
Section: Introductionmentioning
confidence: 99%
“…Under these conditions, body fat was modestly reduced by 1.2 g or 5% in Park2 KO mice, but there was no difference in body weight. Hepatic insulin sensitivity, as assessed by hyperinsulinemic euglycemic clamp, was markedly improved in Park2 KO mice; whereas hyperinsulinemia produced only a 40% reduction in hepatic glucose production in HFD‐fed WT mice, hepatic glucose production was almost completely suppressed (~97%) by insulin in HFD‐fed Park2 KO mice (Costa et al, ). These data demonstrated that Park2 KO mice were protected against diet‐induced hepatic insulin resistance independent of changes in body weight, but the underlying mechanism was not addressed.…”
Section: Introductionmentioning
confidence: 99%